Cost reduction study of automotive part using DFA method : rear lamp - Mohd Hafizi, Nawi (2010)
This thesis deals with the study of assembly analysis of the rear lamp of a car by using Boothroyd Dewhurst DFA method and Hitachi AEM DFA method. The design for assembly of the rear lamp is analyzed based on design efficiency for both methods and the options available are suggested, analyzed and compared with the original design of the rear lamp. The project aimed to reduce the assembly cost of the rear lamp due to the production cost of the rear lamp in industries is high and the demand for the product is increased. From the result and discussion of this thesis, option 3 is the best option for the redesign of the rear lamp. For Boothroyd DFA method, design efficiency for option 3 is 65.7% while the original design efficiency is 48.9% and the design efficiency increased by 16.8%. Then, for Hitachi AEM DFA method, the design efficiency for option 3 is 83.3% while the original design efficiency is 75.7% and the design efficiency increased by 7.6%. The option of redesign with the higher percentage value of design efficiency is selected as the best design in term of its assembly efficiency.